Dimerization of Neuronal Calcium Sensor Proteins - Ames, James B. (Frontiers in Molecular Neuroscience, 2018)
Neuronal calcium sensor (NCS) proteins are EF-hand containing Ca2+ binding proteins that regulate sensory signal transduction. Many NCS proteins (recoverin, GCAPs, neurocalcin and VILIP1) form functional dimers under physiological conditions. The dimeric NCS proteins have similar amino acid sequences (50% homology) but each bind to and regulate very different physiological targets. Retinal recoverin binds to rhodopsin kinase and promotes Ca2+-dependent desensitization of light-excited rhodopsin during visual phototransduction. The guanylyl cyclase activating proteins (GCAP1-5) each bind and activate retinal guanylyl cyclases (RetGCs) in light-adapted photoreceptors. VILIP1 binds to membrane targets that modulate neuronal secretion. Here I review atomic-level structures of dimeric forms of recoverin, GCAPs, and VILIP1. The distinct dimeric structures in each case suggest that NCS dimerization may play a role in modulating specific target recognition. The dimerization of recoverin and VILIP1 is Ca2+-dependent and enhances their membrane-targeting Ca2+-myristoyl switch function. The dimerization of GCAP1 and GCAP2 facilitate their binding to dimeric RetGCs and may allosterically control the Ca2+-dependent activation of retinal guanylyl cyclases.